2016
DOI: 10.1016/j.obhdp.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Don’t stop believing: Rituals improve performance by decreasing anxiety

Abstract: a b s t r a c tFrom public speaking to first dates, people frequently experience performance anxiety. And when experienced immediately before or during performance, anxiety harms performance. Across a series of experiments, we explore the efficacy of a common strategy that people employ to cope with performance-induced anxiety: rituals. We define a ritual as a predefined sequence of symbolic actions often characterized by formality and repetition that lacks direct instrumental purpose. Using different instanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 86 publications
4
96
1
1
Order By: Relevance
“…Second, Anastasi and Newberg (2008) measured Catholic college students' anxiety before and after a stressful experience and found that those randomly assigned to recite the Rosary, a Catholic set of prayers, experienced greater reduction in anxiety than those assigned to watch a religious video. Third, Brooks et al (2016) experimentally demonstrated that rituals can reduce anxiety by randomly assigning individuals about to engage in high-anxiety performances such as public karaoke singing or high-stakes math tests to do rituals versus other non-ritual control behaviors (e.g., passively waiting or actively trying to calm down). People who did rituals showed fewer physiological signs of arousal (e.g., lower heart rate), reported less anxiety, and, as a result, performed better than people who did not.…”
Section: Emotion Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, Anastasi and Newberg (2008) measured Catholic college students' anxiety before and after a stressful experience and found that those randomly assigned to recite the Rosary, a Catholic set of prayers, experienced greater reduction in anxiety than those assigned to watch a religious video. Third, Brooks et al (2016) experimentally demonstrated that rituals can reduce anxiety by randomly assigning individuals about to engage in high-anxiety performances such as public karaoke singing or high-stakes math tests to do rituals versus other non-ritual control behaviors (e.g., passively waiting or actively trying to calm down). People who did rituals showed fewer physiological signs of arousal (e.g., lower heart rate), reported less anxiety, and, as a result, performed better than people who did not.…”
Section: Emotion Regulationmentioning
confidence: 99%
“…For example, one study by Brooks et al (2016) found that engaging in behaviors labeled as "ritual" mitigated performance anxiety, compared to doing the exact same behaviors Psychology of Rituals 18 not labeled as ritual. Presumably, labeling the same behaviors as a ritual created a belief that they were meaningful, which played a critical role in reducing anxiety.…”
Section: Emotion Regulationmentioning
confidence: 99%
“…Much like rituals, emotions serve both intraand interpersonal functions (Ekman 1992;Shariff and Tracy 2011); moreover, several research streams have suggested that engaging in rituals offers a wide array of emotional benefits for both individuals and groups. For example, rituals help people cope with grief (Norton and Gino 2014), regulate emotions (Boyer and Liénard 2008), reduce anxiety before performance (Brooks et al 2016), and amplify holiday enjoyment (Sezer et al 2016). Building on these findings highlighting the link between positive emotional outcomes and rituals for both individuals and groups, we posit that enacting rituals in the domain of romantic relationships is also associated with emotional benefits for couples: H1: Engaging in relationship rituals is associated with greater positive emotions.…”
Section: Theoretical Frameworkmentioning
confidence: 91%
“…Second, Anastasi and Newberg (2008) measured Catholic college students' anxiety before and after a stressful experience and found that those randomly assigned to recite the Rosary, a Catholic set of prayers, experienced greater reduction in anxiety than those assigned to watch a religious video. Third, Brooks et al (2016) experimentally demonstrated that rituals can reduce anxiety by randomly assigning individuals about to engage in high-anxiety performances such as public karaoke singing or high-stakes math tests to do rituals versus other nonritual control behaviors (e.g., passively waiting or actively trying to calm down). People who did rituals showed fewer physiological signs of arousal (e.g., lower heart rate), reported less anxiety, and, as a result, performed better than people who did not.…”
Section: Proposition 2: Rituals Reduce Emotional Deficitmentioning
confidence: 99%